2006
DOI: 10.1096/fj.06-6620com
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the intestinal glucose transporter GLUT2 by flavonoids

Abstract: We tested whether the dominant intestinal sugar transporter GLUT2 was inhibited by intestinal luminal compounds that are inefficiently absorbed and naturally present in foods. Because of their abundance in fruits and vegetables, flavonoids were selected as model compounds. Robust inhibition of glucose and fructose transport by GLUT2 expressed in Xenopus laevis oocytes was produced by the flavonols myricetin, fisetin, the widely consumed flavonoid quercetin, and its glucoside precursor isoquercitrin [corrected]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

33
331
1
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 395 publications
(367 citation statements)
references
References 55 publications
33
331
1
2
Order By: Relevance
“…Johnston et al [35] demonstrated that certain dietary polyphenols decrease Caco-2 cell glucose uptake, through non-competitive inhibition of GLUT-2 transporters. This finding was confirmed by Kwon et al [36] and Song et al [37]. In this study, despite the decreased glucose uptake, there was a rise in p47phox mRNA expression that reflects the pro-oxidant nature of the AE.…”
Section: Discussionsupporting
confidence: 88%
“…Johnston et al [35] demonstrated that certain dietary polyphenols decrease Caco-2 cell glucose uptake, through non-competitive inhibition of GLUT-2 transporters. This finding was confirmed by Kwon et al [36] and Song et al [37]. In this study, despite the decreased glucose uptake, there was a rise in p47phox mRNA expression that reflects the pro-oxidant nature of the AE.…”
Section: Discussionsupporting
confidence: 88%
“…Therefore, since GLUT5 is considered to be a fructose transporter in vivo, with only a low affinity for glucose [25], and GLUT1 protein levels in the renal tubule are generally considered to be reduced [26,27] or unchanged in diabetes [9], it is reasonable to hypothesise that GLUT2 might be responsible for glucose-induced tubular cell hypertrophy in diabetes. Indeed, two indirect findings also suggest a potential pathophysiological link between GLUT2 function and the kidney: one is the finding of renal hypertrophy and glomerulopathy in patients with GLUT2 mutations in the Fanconi-Bickel syndrome [28]; the other is the recent observation that flavonoids, which are known to ameliorate the changes of diabetic nephropathy in experimental models [29], inhibit GLUT2 production [30]. It is intriguing to speculate whether the beneficial effects of flavonoids in diabetes may be related, in part, to an inhibitory effect on GLUT2 in the kidney (and small intestine).…”
Section: Discussionmentioning
confidence: 99%
“…Pelargonidin and pelargonidin-3-glucoside inhibit glucose absorption (1 mM), with IC 50 = 1·34 and 2·47 mM respectively, in oocytes expressing SGLT1 (57) . In a separate in vitro study using Xenopus oocytes expressing GLUT2, Kwon et al (91) were not able to detect an inhibitory effect on glucose uptake (10 mM) when testing delphinidin and cyanidin (0-300 µM), although their glycosidic forms were not tested and other flavonoids present in berries were observed to inhibit GLUT2-mediated glucose transport.…”
Section: Glucose Uptake: In Vitro Studiesmentioning
confidence: 97%